Influence of Habitat and Land Use on the Assemblages of Ephemeroptera, Plecoptera, and Trichoptera in Neotropical Streams. Issue 1 (19th May 2015) - Amaral, Pedro Henrique Monteiro do; Silveira, Lidimara Souza da; Rosa, Beatriz Figueiraujo Jabour Vescovi; Oliveira, Vívian Campos de; Alves, Roberto da Gama
Abstract : Insects of the orders Ephemeroptera, Plecoptera, and Trichoptera (EPT) are often used to assess the conditions of aquatic environments, but few studies have examined the differences in these communities between riffles and pools. Our objective was to test whether riffles shelter greater richness and abundance of EPT, as well as to assess the sensitivity of these insects for detecting impacts from different land uses in streams in southeastern Brazil. Samples were collected in the dry season of 2012 with a Surber sampler in riffles and pools of nine streams (forest, pasture, and urban areas). Principal component analysis distinguished the streams according to different land uses as a function of percentage of plant cover and water oxygenation level and showed partial distinction between riffles and pools as a function of current speed and percentage of ultrafine sand. Detrended correspondence analysis indicated the distinction in EPT composition between riffles and pools, except in urban streams. The results of this study confirm the expected differences in the EPT fauna structure between riffles and pools, especially in forest and pasture environments. The individual metrics of riffle and pool assemblages showed significantly different responses to land use. Therefore, we suggest individual sampling of riffles and pools, since the metrics of these assemblages' insects can differ between these habitats and influence the results of assessments in low-order streams.